Policy Formulation of Financial Management Patterns With Sharia Principles in Bogor City Hospital - Armein Sjuhary Rowi; Mukhaer Pakkanna (Faculty of Social Science, Universitas Negeri Padang, 2023)
Good financial management by minimizing findings is determined by the selection of the right model. This study aims to develop a policy formula for financial management patterns with Sharia principles in the Bogor City Regional General Hospital. The qualitative research method uses the decision-making method with Analytic Network Process (ANP) to determine the financial management policy model with Sharia principles. This research was conducted through interviews and focus group discussions. The results obtained show that the Islamic financial management model, in part, has the highest priority with cluster restrictions reaching 0.191007. So that the chosen Islamic financial management formula is financial management with partial Islamic principles. This research provides a new breakthrough regarding the application of Sharia policy. The application of Sharia can be carried out in stages with the Sharia model in advance. This will have an impact on the ease of implementing Sharia because it does not need to be full of all the difficulties. Partial implementation of Sharia is still considered a strong enforcement effort to step up to become perfect Sharia.